Hyperuricemia Is Associated With the Risk of Atrial Fibrillation Independent of Sex: A Dose-Response Meta-Analysis - Xiong, Jianhua; Shao, Wen; Yu, Peng; Ma, Jianyong; Liu, Menglu; Huang, Shan; Liu, Xiao; Mei, Kaibo (Frontiers in Cardiovascular Medicine, 2022)
Background: Conflicting findings of the association between serum uric acid (SUA) and atrial fibrillation (AF) have been reported in both men and women. The sex-specific associations between SUA and the risk of AF are unclear, although hyperuricemia is independently associated with the risk of AF. We performed this meta-analysis to assess the sex-specific effect of SUA on the risk of AF. Methods The PubMed, EMBASE, and Cochrane Library databases were searched up to October 3, 2021, for studies that reported sex-specific associations of SUA levels with AF. Linear relationships were assessed by the generalized least squares trend estimation. This study was registered with PROSPERO (42020193013). Results Ten eligible studies with 814,804 participants (415,779 men and 399,025 women) were identified. In the category analysis, high SUA was associated with an increased risk of AF in both men (OR: 1.42; 95% CI, 1.18–1.71, I2 = 34%) and women (OR: 2.02; 95% CI, 1.29–3.16, I2 = 70%). In the dose-response analysis, for each 60 μmol/L (1 mg/dL) increase in the SUA level, the risk of AF increased by 15% (OR: 1.15; 95% CI, 1.07–1.25, I2 = 74%) in men and 35% (OR: 1.35; 95% CI, 1.18–1.53, I2 = 73%) in women. There was a borderline difference in the impact of SUA on the risk of AF between men and women (P for interaction = 0.05). A significant linear relationship between SUA and the risk of AF was observed in men (P for non-linearity = 0.91) and women (P for non-linearity = 0.92). Conclusions This study suggested that there was a significant linear relationship between SUA and the risk of AF among men and women, with a higher risk estimate for women. Additional trials are required to assess the effect of reduced SUA therapy on AF incidence. Systematic Review Registration https:www.crd.york.ac.uk/PROSPERO/, identifier: CRD 42020193013.